THE POTENTIAL OF GREEN VILLAGE TOURISM DEVELOPMENT ON THE SACRED STREET OF BANJARMASIN CITY - Andri yuli (JURNAL SOCIUS, 2021)
This study aims: (I) to determine the potential for the development of green village tourism, (2) strategies to develop the tourism potential of the green village so that it becomes a tourist attraction.The research method used in this research is qualitative. The data source was selected by purposive sampling. Data collection was carried out using observation, interview and documentation techniques. Analysis of research results using data reduction steps, display, and verification. The results of this study indicate that: (I) the development potential of a green village, namely the development of a green village, is carried out by the government entirely to change the riverbanks that originally looked slum into a beautiful one, (2) The strategy for developing the potential for village tourism is carried out by the community and the government with how to promote through social media and hold events such as competitions in the green village.